2015
DOI: 10.1109/tnsre.2015.2388692
|View full text |Cite
|
Sign up to set email alerts
|

Stretch Evoked Potentials in Healthy Subjects and After Stroke: A Potential Measure for Proprioceptive Sensorimotor Function

Abstract: Abstract-Sensory feedback is of vital importance in motor control, yet rarely assessed in diseases with impaired motor function like stroke. Muscle stretch evoked potentials (StrEPs) may serve as a measure of cortical sensorimotor activation in response to proprioceptive input. The aim of this study is: 1) to determine early and late features of the StrEP and 2) to explore whether StrEP waveform and features can be measured after stroke.Consistency of StrEP waveforms and features was evaluated in 22 normal sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 38 publications
4
10
0
Order By: Relevance
“…Examples of an even nonlinear function are y(u)=u 2 , y(u)=u 4 and y(u)=abs(u). Seiss et al [32] and Campfens, et al [33] showed that a stretch of respectively the finger and wrist resulted in a similar ERP for both flexion and extension direction, which also indicates an even nonlinear relation.…”
Section: A Quantification Of the Nonlinear Contributionsmentioning
confidence: 95%
“…Examples of an even nonlinear function are y(u)=u 2 , y(u)=u 4 and y(u)=abs(u). Seiss et al [32] and Campfens, et al [33] showed that a stretch of respectively the finger and wrist resulted in a similar ERP for both flexion and extension direction, which also indicates an even nonlinear relation.…”
Section: A Quantification Of the Nonlinear Contributionsmentioning
confidence: 95%
“…In the central nervous system, cortical responses to muscle stretch have been investigated by previous studies using the event-related potential (ERP) (Abbruzzese et al, 1985 ; Campfens et al, 2015 ). The latencies and topographies of the stretch-evoked ERP reflect the time courses of cortical activity and most active areas in response to the muscle stretch.…”
Section: Introductionmentioning
confidence: 99%
“…The latencies and topographies of the stretch-evoked ERP reflect the time courses of cortical activity and most active areas in response to the muscle stretch. Both early (<100 ms post-perturbation onset) and late (>100 ms) ERP components were reported around the contralateral motor cortex (Campfens et al, 2015 ). Considering the efferent motor conduction delay (~20 ms), the early cortical response is thought to related to the rapid transcortical muscle reaction to the perturbation (<~120 ms) while the late cortical response may be related to the slow transcortical muscle reaction (>~120 ms) (MacKinnon et al, 2000 ; Pruszynski and Scott, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Combining peripheral perturbations with neurophysiological measurements like Electro Encephalography (EEG) yields properties of the sensor-controller-motor loop in more detail. Assessing cortical responses to fast muscle stretches yields stretch Evoked Potentials (strEP) that may serve as a measure of cortical sensorimotor activation in response to proprioceptive input (Campfens et al, 2015a ). Afferent sensory pathway information transfer and processing can be assessed by calculation of the coherence between cortical activity and a peripheral position perturbation (position-cortical coherence, PCC; Campfens et al, 2015b ).…”
Section: Control and Plant Interactionmentioning
confidence: 99%
“…Afferent sensory pathway information transfer and processing can be assessed by calculation of the coherence between cortical activity and a peripheral position perturbation (position-cortical coherence, PCC; Campfens et al, 2015b ). Aforementioned measures are disturbed in stroke patients and may be used to detect integrity of afferent and efferent pathways separately and propagation of signals over the cortex (Campfens et al, 2015a , b ). High density EEG may further reveal cortical involvement and its location in motor tasks (Yao and Dewald, 2005a ; Yao et al, 2005b ).…”
Section: Control and Plant Interactionmentioning
confidence: 99%